Kesulitan Pembelajaran Daring Menuju Luring di UPTD SD Negeri Banyuajuh 5 - Aini, Syarifa; Fatinah, Titin; Setyawan, Agung (Almeera Education, 2022)
This study aims to determine the difficulties and changes in the online learning process during the Covid-19 period to offline for elementary school students. This study uses a qualitative method, namely by direct observation and interviews with educators and elementary school students, so that the authenticity of this article can be maintained. The purpose of this research article is to determine the adaptation of online to offline learning, online learning constraints, changes in learning systems, the impact of online learning, and solving student learning problems and offline learning processes. The results of this study are so that we as educators can find out what problems are being faced by students so that educators can provide solutions and problem solving for students so that they can run smoothly in the learning process, so that students will not experience learning difficulties where learning difficulties can occur. have an impact on the psychology or psychology of students, if the psychology of students is disturbed then students will experience psychological disorders that make the teaching and learning process hampered.